2023
DOI: 10.3390/vaccines11020481
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Associated Factors of SARS-CoV-2 Infection Post-mRNA-1273 Booster Vaccination in Health-Care Workers

Abstract: The COVID-19 pandemic has caused significant morbidity and mortality worldwide, especially among health-care workers. One of the most important preventive measures is vaccination. This study examined factors associated with the incidence rate of SARS-CoV-2 infection after mRNA-1273 booster vaccination (preceded by the CoronaVac primary vaccination) and the antibody profile of health-care workers at one of the tertiary hospitals in Indonesia. This was a combined retrospective cohort and cross-sectional study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…The results revealed no significant differences in the proportions of individuals who contracted COVID-19 based on sex or age. This is consistent with the findings of other studies on COVID-19 incidence among healthcare workers [ 37 ] but different from the findings of the studies concerning the general population, where males were reported to be more affected than females [ 38 ]. The lack of difference for healthcare workers can be attributed to their commonly high level of professional medical training that was indifferent to sex or age.…”
Section: Discussionsupporting
confidence: 83%
“…The results revealed no significant differences in the proportions of individuals who contracted COVID-19 based on sex or age. This is consistent with the findings of other studies on COVID-19 incidence among healthcare workers [ 37 ] but different from the findings of the studies concerning the general population, where males were reported to be more affected than females [ 38 ]. The lack of difference for healthcare workers can be attributed to their commonly high level of professional medical training that was indifferent to sex or age.…”
Section: Discussionsupporting
confidence: 83%
“…To date, more than 200 COVID-19 vaccine candidates are in various stages of development, and more than 50 of these candidates have started clinical trials. These candidates may use inactivated or live attenuated viruses, nucleic acids (DNA or RNA), viral vectors, recombinant proteins or virus particles [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. WHO is committed to keeping the momentum for boosting access to COVID-19 vaccinations going and will continue to assist countries in expediting vaccine delivery in order to save lives and prevent people from becoming seriously ill.…”
Section: Introductionmentioning
confidence: 99%